The possibility of using laser and micro-jet technology in the welding of structural elements of vehicles - Wojciech MAJEWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
A paper presents the possibility of laser welding using micro-jet cooling. The effect of micro-jet cooling on microstructure and mechanical properties of the weld metal deposit was carried out. New welding process was analyzed for use in the automotive industry. Studies have confirmed the positive effect of cooling micro-jet cooling both for the MIG welding and laser welding.